Development of a ChatGpt Script-Based Learning Website for Arabic Language Learning at Nurul Huda Middle School, Malang City - Muhammad Yushfa Dzihni; Imam Asrori; Moh. Fauzan (Al-Fusha : Arabic Language Education Journal, 2026)
This study aims to develop an Arabic language website learning media (Arabic9 Fun) using Artificial Intelligence script (ChatGPT) to address the low mastery of language skills of ninth grade junior high school students. The research method used Research and Development (R&D) with the ADDIE model. Data were collected through expert questionnaires, teacher assessments, and tests (pretest-posttest) on 20 students at Nurul Huda Junior High School Malang. The results of the study proved that ChatGPT successfully functioned as a developer assistant in compiling the entire website script. The feasibility test obtained a score of 94.54% (material experts), 92% (media experts), and 92% (teachers), so it was categorized as very feasible and practical. The effectiveness test showed an increase in student scores from 69.90 to 80.70 with an N-Gain score of 0.36 (moderate category). In conclusion, the Arabic9 Fun website is very feasible and quite effective in improving the Arabic language learning outcomes of junior high school students.